Student Team Achievement Division (STAD) Technique to Improve the Listening Comprehension of the Second Year Students of SMP N 14 Pekanbaru - Missi Tri Astuti Tri Astuti; Fadly '; Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is a classroom action research that was conducted based on the problem occurred at the second year student of SMP Negeri 14 Pekanbaru, namely the students were lack of practice in listening descriptive and recount text and this situation made them got poor score in test. Therefore, this research was aimed at studying the improvement on the ability of the second year students of SMP Negeri 14 Pekanbaru in listening comprehension by using STAD. Besides, this research was also intended to identify the components of listening comprehension are mostly improved after being taught by using STAD. The participants were 28 students from VIII class of SMP N 14 Pekanbaru. This research was conducted in 2 cycles. The data collection technique were obtained through (1) observation sheet which was applied to know the students’ activities during teaching and learning process, (2) test was done to measures students’ achievement, and (3) field note was done to obtain information about teacher, the students’ activities and performance during the implementation of STAD. The research findings can be briefly explained as follow: first, the students’ listening ability could be improved by using STAD. Before the research was done, the average score of the students’ listening was only 44.25. After the research done for cycle 1, it improved to 66. In cycle 2, it increased up to 79. Second, the students’ activeness during the treatments by STAD also improved from one meeting to others. The observation sheet and field note result showed that the used of STAD make the teaching process more effective and it also helped students improve their listening ability and more active in learning process.Keywords: STAD, Students’ Listening Ability, Descriptive and Recount Text